Pengaruh E-trust, Online customer review dan Online customer rating Terhadap Keputusan Pembelian pada E-commerce Tokopedia (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Ahmad Abiyu Tsani; Jeni Susyanti; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract People in Indonesia do not fully feel safe or comfortable due to the high number of fraudulent online transaction cases. There is a discrepancy between online customer reviews and online customer ratings and the inability of buyers to contact directly with sellers so that the goods to be purchased can only be seen with product descriptions and pictures reducing e-trust in making purchasing decisions. This study aims to analyze the effect of e-trust, online customer reviews, and online customer ratings on purchasing decisions at Tokopedia e-commerce. This research uses quantitative methods. Non-probability sampling was used with a purposive sampling technique as a sample of 105 respondents. Tests carried out are instrument tests, classical assumption tests, multiple linear analysis tests, and hypothesis testing with the application of software SPSS 25. The results of this study demonstrates that (1) e-trust has a significant impact on Tokopedia e-commerce purchasing decisions, (2) online customer reviews have a significant impact on Tokopedia e-commerce purchasing decisions, and (3) online customer ratings have a significant impact on Tokopedia e-commerce purchasing decisions. Keywords: E-trust, Online customer review, Online customer rating, Purchasing Decision